Contribution to the Vascularization of Cruciate Knee Ligaments and its Relevance in Trauma Surgery (International Journal of Medical and Surgical Sciences, 2014)
The intercondyloid notch of the knee, has acquired interest from the surgical point of view, with the use of technical arthroscopy in the treatment of anterior and posterior cruciate ligaments. This review shows the arterial branches that receive cruciate ligaments in different areas and confirms the presence of periligamentous anastomotic networks. The study included 6 adult knees and 14 fetal human knees between the 6th and 8th month of gestation, for artery and cruciate ligament analysis through transverse and frontal slice dissections. In conclusion cruciate ligaments receive their principal vascular contribution, through the medial artery of the knee and secondarily from inferior medial and lateral arteries. In the fetal stage there were periligamentous arterial connections in the femoral insert of both ligaments. Anatomical knowledge of the arteries that approach cruciate ligaments is important in repairs as it favors vitality and good joint mechanics.